Diabetes related knowledge, self-care behaviours and adherence to medications among diabetic patients in Southwest Ethiopia: a cross-sectional survey. Issue 1 (December 2016) - Kassahun, Tefera; Gesesew, Hailay; Mwanri, Lillian; Eshetie, Tesfahun
Abstract Background The provision of health education involving self-care and good adherence to medications has been acknowledged to be a cost effective strategy for improving quality of life of diabetes patients. We assessed levels of knowledge about type 2 diabetes mellitus (T2DM), self-care behaviours and adherence to medication among DM patients. Methods A facility based cross-sectional survey of 325 adults with T2DM patients attending Jimma University Teaching Hospital, Southwest Ethiopia was conducted. We used diabetes Knowledge Test, Expanded Version of the Summary of Diabetes Self-Care Activities and Morisky 8-Item medication adherence as tools to measure diabetic knowledge, self-care behaviours and adherence to medications respectively. Multinomial logistic regression analyses were used to assess the independent predictors of diabetes knowledge and adherence to medications. The binary logistic regression was applied for self-care behaviours. Results 309 respondents were included in the survey. Of all the respondents, 44.9 %, 20.1 % and 34.9 % had low, medium and high level diabetic knowledge respectively. High level of diabetic knowledge was the reference group. Being illiterate (AOR = 3.1, 95%CI: 1.03-9.3), having BMI <18 kg/m2 (AOR = 6.4, 95%CI: 1.2-34.9) and duration of DM < 5 years (AOR = 4.2, 95%CI: 1.9-9.5) were significantly associated with low level of diabetic knowledge. T2DM patients who practiced good self-care (AOR = 0.5, 95%CI: 0.3-0.9) were less likely to have low knowledge. Duration of DM < 5 years (AOR = 9.8, 95%CI: 3.2-30.2) was significantly associated with medium level of diabetic knowledge. 157(50.8 %) patients had poor self-care behaviour and this was associated with level of education and adherence to medication. The proportions of patients with low, medium and high adherence to medication were 24.9 %, 37.9 % and 37.2 % respectively. Being a merchant, having medium level of diabetic knowledge and having good glycemic control level were associated with low adherence to medications. Conclusions Significant number of DM patients had low level of knowledge, poor self-care behaviours and low level of adherence to medications. These findings call for the need of integrated interventional management on diabetic knowledge, self-care behaviours and adherence to medications. To ensure effective T2DM management, a strategic approach that improves health literacy could be a cross cutting intervention.